Language Style in the Lyrics of the Song “ Virus Corona “, “Bencana”, and “Suratan” by Rhoma Irama - Puji Astuti Sri (EDP Sciences, 2021)
Song lyrics can be used to communicate the author’s message to others. The songwriter can express what he feels, sees, and experiences. The song lyrics by Roma Irama are fascinating in terms of language style. Therefore, the purpose of this research is to describe the language style used in the lyrics of Rhoma Irama’s songs “Virus Corona,” “Bencana,” and “Suratan.” This study used the data in the form of song lyrics snippets from the three songs. The data was gathered through the listening method, which involved listening to the three songs displayed on YouTube. The lyrics of the songs were then recorded and analyzed using stylistic theory. According to the study’s findings, the language styles used in the lyrics of “Virus Corona,” “Bencana,” and “Suratan” are climax, parallelism, antithesis, anaphor, asyndeton, pleonasm, rhetorical questions, paraphrases, litotes, metaphors, and cynicism. As a result, Rhoma Irama employs a variety of language styles in the lyrics of his three songs.